The community «siege» to the nationality jurisdiction of member states: the ECJ judgement of 18 January 2022 - Juárez Pérez, Pilar (CUADERNOS DE DERECHO TRANSNACIONAL, 2022)
An EU citizen, originally from Estonia and residing in Austria, renounces her nationality of origin in order to acquire that of her State of residence. The resignation is effective and despite the Austrian authorities guaranteeing naturalization, they end up considering that the interested party has incurred in administrative infractions that constitute a legal reason for not granting nationality. Specifically, the applicant had been sanctioned for not affixing the technical vehicle inspection control badge to her car and for driving under the influence of alcohol. As a consequence, it is doomed to a situation of involuntary statelessness, considered by the CJEU incompatible with the principle of proportionality that must inspire any state measure that affects the nationality of a member country, and therefore, the fundamental status of citizen of the Union.